L.E.D. VOLUME UNIT METER: A PRACTICAL AID FOR RADIO‐TELEMETRY RESEARCH - Frank H. Rice (Wildlife Society Bulletin)
Abstract: A light emitting diode (L.E.D.) volume unit meter was developed and used to locate and monitor the activity of radio‐instrumented eastern wild turkeys (Meleagris gallopavo silvestris). The L.E.D. volume unit meter is especially valuable for use with radio‐telemetry receivers that otherwise provide no visual means for an operator to interpret signal strength from a radio transmitter. The unit converts the audio signal produced by radio‐telemetry receivers into a visual display of L.E.D.s. Maximum signal strength is indicated by the greatest number of L.E.D.s flashing on the unit's display. The L.E.D. volume unit meter also functions as an activity monitor. By interpreting the flashing display of L.E.D.s, it is easy for an operator to determine the active/inactive status of a radio‐instrumented animal. The device was found to be far more accurate than the conventional headphone method in locating radio‐instrumented wild turkeys. Use of the L.E.D. volume unit meter greatly reduces the amount of time it takes to obtain azimuth readings and allows more location data to be collected in a given period of time. The L.E.D. volume unit meter is relatively simple to construct, inexpensive, maintenance‐free, and most importantly, easy to use and interpret. A schematic and explanation of the circuitry is provided.